Starsi ludzie jako segment rynku reklamy w Polsce - Widerski, Jerzy (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
For the purpose of this publication, current advertisements, in which there are protagonists symbolizing the older generation, were analyzed. In the publication the author presents the results of analyses of TV commercials broadcast from January 1 to May 15, 2018. The purpose of the observation was first of all to show the image of older people present in commercials and the visual and verbal means used for this purpose. The task of the analysis was also to present social roles assigned to the characters from commercials and the products (categories and sub-categories), which are positioned in these spots. The aim of the article is to show the marketing aspect of old age, which is the buyer model created in current commercials
Keywords: socjologia; marketing; reklama; starość; starzenie się społeczeństwa